THE LAMARTINA SQUARE AND SEVERITY INDEX IN SURGERY FOR HIGH-GRADE LUMBAR LISTHESIS - José Alberto Alves Oliveira; Vinícius Tapie Guerra E Silva; Antonio Eulalio Pedrosa Araujo Junior; Luis Antonio Medeiros Moliterno; Paulo Cesar Almeida; Luis Eduardo Carelli Teixeira da Silva; Ricardo de Souza Portes Meireles (Coluna/Columna, 2023)
ABSTRACT Objective: evaluate the correlation between main sacropelvic alignment measurements and pelvic retroversion reduction and assessing Lamartina Square effectiveness in choosing the proximal instrumentation level. Methods: sample comprising 21 patients with high-grade L5 -S1 spondylolisthesis subjected to arthrodesis with instrumentation from January 2004 to December 2016. Patients’ demographic data, surgery type, complications, sagittal alignment parameters, Severity Index and Lamartina Square were recorded before surgery and in the last follow-up. Data processed in SPSS 22.0, with different means were calculated through Student’s t test, for paired data. Linear correlation analysis was performed based on Spearman’s coefficient. P <0.05 was statically significant. Results: there was significant improvement in the slip and Dubousset’s lumbosacral kyphosis angles (> 100° in the last postoperative follow-up). There was significant reduction of slip rate ( and in the L4 and L5 Severity Index, which highlighted strong correlation to pelvic tilt, mismatch and slip angle. Severity index also showed strong inverse correlation between Dubousset’s lumbosacral kyphosis angle and sacral slope. Conclusion: L5 Severity Index and Lamartina Square are important variables for preoperative planning of patients with high-grade lumbar spondylolisthesis. Level of Evidence IV; Case Series.